[Penguins and Person Along Londrangar Coast] - Streng, Evelyn Fiedler (1975)
Photograph of penguins at Londrangar on Snæfellsnes Peninsula. Two penguins with wide, orange beaks sits on a black lava rock along blue water below a grassy cliff. A person in a green jacket with a red and blue hat kneels down on the cliff side, looking at the penguins.